Fabrication of Amino-Functionalized CAU-1/ Cellulose Acetate Mixed Matrix Membranes for CO2/N2 Separation - Yeong, Y.F. (Trans Tech Publications Ltd, 2019)
In this work, a new type of mixed matrix membranes comprising of amino-functionalized CAU-1 as filler and cellulose acetate as polymer phase were fabricated for CO2 separation from N2. The crystallinity and morphology of the resultant fillers were verified by using X-ray diffraction (XRD) and scanning electron microscope (SEM). The energy-dispersive X-ray (EDX) results showed that, sedimentation and agglomeration of fillers were found at loading of more than 5 wt. Subsequently, the gases permeation results revealed that, an increase in CO2 permeability and CO2/N2 selectivity of 149 and 81, respectively, were achieved for the membrane loaded with 5 wt of CAU-1-NH2, as compared to pure cellulose acetate membrane. Â© 2019 Trans Tech Publications Ltd, Switzerland.